Internet of Things and healthcare system: A systematic review of ethical issues - Somayyeh Zakerabasali; Seyed Mohammad Ayyoubzadeh (Health Science Reports, 2022)
Abstract Background and Aims The Internet of Things (IoTs) is a set of connected objects and devices that share data and pursue a common goal in different areas. IoT technology can significantly help the healthcare system by enabling the monitoring of elderly and chronic disease patients. Along with the growth of this technology, its challenges and limitations such as Connectivity, Compatibility, Standards, cost, legal, and ethical also increase. One of the most critical and challenging issues in the IoT is ethical issues. This study aims to explore the key ethical aspects of the IoT and Categorize them based on the executive phases of IoT in healthcare. Methods The current study was conducted in two phases using the mixed‐method approach. In the first phase, a systematic review was conducted in relevant databases to identify ethical issues of the IoT. In the second phase, a focus group discussion was conducted to classify the extracted data elements based on executive phases of IoT by medical informatics experts and computer engineerings. Results Among the 138 papers retrieved through the search strategy, 11 articles were selected, and 12 ethical issues related to IoT were identified. The obtained results revealed the importance of ethical issues of IoT, including security, confidentiality, privacy, anonymity, freedom to withdraw, informed consent, integrity, availability, authorization, access control, censoring, and eavesdropping. They were classified into five main categories of executive phases of IoT based on the five experts’ opinions affiliated with SUMS, including data collection, data storage, data process, data transmission, and data delivery. Conclusion Because of the key role of the IoT in disease prevention, real‐time tele‐monitoring of patient's functions, testing of treatments, health management, and health research, considering the risks relating to Health care and patient data is essential. Moreover, health policymakers should be aware of the ethical commitment to using IoT technology.